2014
DOI: 10.1038/nature13295
|View full text |Cite
|
Sign up to set email alerts
|

BRCA1 controls homologous recombination at Tus/Ter-stalled mammalian replication forks

Abstract: Replication fork stalling can promote genomic instability, predisposing to cancer and other diseases1–3. Stalled replication forks may be processed by sister chromatid recombination (SCR), generating error-free or error-prone homologous recombination (HR) outcomes4–8. In mammalian cells, a long-standing hypothesis proposes that the major hereditary breast/ovarian cancer predisposition gene products, BRCA1 and BRCA2, control HR/SCR at stalled replication forks9. Although BRCA1 and BRCA2 affect replication fork … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
197
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 136 publications
(214 citation statements)
references
References 33 publications
8
197
1
Order By: Relevance
“…We found previously that Tus F140A induces higher levels of HR than wtTus in mammalian cells carrying a 6xTer array HR reporter. 15 This suggests that the C6 base-flipping lock mechanism is not required for Tus/Ter-induced HR in mammalian cells and that the affinity of Tus for duplex Ter is the critical determinant of HR induction in mammalian cells. In contrast, Larsen et al found that Tus/Ter mediates polar replication fork arrest in Saccharomyces cerevisiae.…”
Section: Introductionmentioning
confidence: 89%
See 4 more Smart Citations
“…We found previously that Tus F140A induces higher levels of HR than wtTus in mammalian cells carrying a 6xTer array HR reporter. 15 This suggests that the C6 base-flipping lock mechanism is not required for Tus/Ter-induced HR in mammalian cells and that the affinity of Tus for duplex Ter is the critical determinant of HR induction in mammalian cells. In contrast, Larsen et al found that Tus/Ter mediates polar replication fork arrest in Saccharomyces cerevisiae.…”
Section: Introductionmentioning
confidence: 89%
“…16 The Tus/6xTer replication fork barrier was »70% effective in blocking the mammalian replisome in this setting. 15 Unexpectedly, encounter of the mammalian replisome at the permissive end of the Ter array also causes replisome arrest, indicating that fork arrest at a Tus/6xTer replication fork barrier in mammalian cells is at least in part non-polar. By placing the 6xTer array within a reporter of mammalian HR, targeted to a specific locus of mouse embryonic stem (ES) cells, we found that transient expression of wild type Tus triggers HR at the 6xTer array, while expression of a mutant form of Tus (H144A) that has a low affinity for Ter failed to induce HR in the same cells.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations